2018
DOI: 10.2139/ssrn.3100645
|View full text |Cite
|
Sign up to set email alerts
|

Do Alpha Males Deliver Alpha? Testosterone and Hedge Funds

Abstract: Using facial width-to-height ratio (fWHR) as a proxy for testosterone, we show that high-testosterone hedge fund managers significantly underperform low-testosterone hedge fund managers after adjusting for risk. Moreover, high-testosterone managers are more likely to terminate their funds, disclose violations on their Form ADVs, and exhibit greater operational risk. We trace the underperformance to high-testosterone managers' greater preference for lottery-like stocks and reluctance to sell loser stocks. Funds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 114 publications
(186 reference statements)
0
2
0
Order By: Relevance
“…For example, Cesarini et al (2010) find that approximately 25% of individual variation in financial decision making is due to genetic variation. Prior literature on innate characteristics has also focused on CEOs (see for example Dikolli et al 2012;Jia et al 2014;Graham et al 2013), and money managers (Brown et al 2018;Lu and Teo 2018). The current study is one of the first to extend this literature by focusing on analysts.…”
Section: Introductionmentioning
confidence: 90%
“…For example, Cesarini et al (2010) find that approximately 25% of individual variation in financial decision making is due to genetic variation. Prior literature on innate characteristics has also focused on CEOs (see for example Dikolli et al 2012;Jia et al 2014;Graham et al 2013), and money managers (Brown et al 2018;Lu and Teo 2018). The current study is one of the first to extend this literature by focusing on analysts.…”
Section: Introductionmentioning
confidence: 90%
“…Several recent studies have looked at very specific dark traits associated with personality disorders. Lu and Teo (2018) for example, found that high testosterone, masculine hedge fund managers were less successful as they had a preference for lottery-like stocks and were reluctant to sell losing stocks. Noe and Vulkan (2018) argued that investment decisions are usually made in a group context.…”
Section: Investment Management: the Dark Sidementioning
confidence: 99%